Children Safety: Education Game for Childs Sex Education - Fajar As'ari; Hendra Prasetya; Ridwan Sanjaya (Soegijapranata Catholic University, 2016)
Some people still cannot talk freely about sex education. On the other hand, some of them have an assumption about teaching sex education will leads to free sex behavior. Sometimes parent afraid to talk about sex education with their children, even some parent think sex education is not important thing for children.However, in fact children need to know about sex education for their own good. To children, sex education is to explain differences in male and female and to know well about themselves. Create media to deliver sex education is the way to teach children about sex education. Among many media, game is one option to deliver this education.This research will discuss about game for childs sex media education. Use game as sex media education because game has capability to deliver message. Through game concept, picture, and animation, game deliver childs sex education to children. With the objective to prevent child from sexual abuse. However, when children play the game they need companion to make clear that children understand the meaning of game message through game story.